RECEPCJA TWÓRCZOŚCI JÓZEFA WITTLINA PO 1989 ROKU - Zych-Chludzińska, Magdalena (Colloquia Litteraria, 2016)
The article surveys the current state of research on Józef Wittlin’s works. It examines and summarizes evidence of the reception of his writings after 1989. The name of the writer remains obscure to Polish readership, while opinions about his works do not go beyond trite phrases. Wittlin’s debut work, Hymny, is overlooked by critics, his essays await edition, and Sól Ziemi – Wittlin’s greatest achievement – unjustly became a forgotten novel.